IMPLEMENTASI CITES (CONVENTION ON INTERNATIONAL TRADE ENDAGERED SPECIES OF WILD FLORA AND FAUNA) DI INDONESIA DALAM MENGATASI KEPUNAHAN RAMIN OLEH PERUSAHAAN ASIA PULP AND PAPER - Affiani, Ririn; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is about the implementation of CITES (Convention on International Trade in Endagered Species of Wild Flora and Fauna) against the Indonesian government policy. In particular, this research is aiming to look at the extent of influence CITES againts Indonesian policy related to the extinction ramin conducted by Asia Pulp & Paper (APP)This research is using the perspective of liberalism. The level of analysis that is being used is the level of analysis of the Nation-State. CITES does have a major influence in Indonesia’s decision making; however, Indonesia is still the major actor in the domestic and international affairs. The theory used is the theory of international cooperation.Ramin legally protected under Indonesian law and CITES regulations that have been adopted by the Indonesian government. Since Indonesia banned ramin logging and trade in 2001, more than a quarter of ramin habitat has been clearcut by APP. In 2001, Indonesia put ramin population on Appendix III of CITES, and give a mandate to the importing countries to stop the import of ramin illegally exported. In 2004, given the continual loss of habitat and illegal logging ramin, Ministry of Forestry asked countries to CITES to include all species of ramin to list higher Appendix II, which requires more stringent control of trade, in an effort to achieve improved enforcement of the ban on exports through international monitoring of potential violations of trade under CITES.Keywords: Ramin, CITES, Environment, Implementation.